2021
DOI: 10.1108/jwl-07-2020-0127
|View full text |Cite
|
Sign up to set email alerts
|

Dwelling within the fourth industrial revolution: organizational learning for new competences, processes and work cultures

Abstract: Purpose This paper aims to address the relevance and impact of the fourth industrial revolution through a theoretical and practical perspective. The authors present both the results of a literature review, highlighting the new competences required in innovative workplaces and a pivotal case, which explores challenges and skill models diffused in industry 4.0, describing the role of proper organizational learning processes in shaping new work cultures. Design/methodology/approach The paper aims to enhance the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(54 citation statements)
references
References 57 publications
1
32
0
4
Order By: Relevance
“…Seeking to explore how to dwell within the Fourth Industrial Revolution, Ivaldi et al (2021) highlight the need to link new technologies and sustainability, pointing out the challenge to deal with the spreading digital revolution. Hecklau et al (2016) underpin four categories of new skills:…”
Section: New Work Culture and Capabilities: Theoretical Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…Seeking to explore how to dwell within the Fourth Industrial Revolution, Ivaldi et al (2021) highlight the need to link new technologies and sustainability, pointing out the challenge to deal with the spreading digital revolution. Hecklau et al (2016) underpin four categories of new skills:…”
Section: New Work Culture and Capabilities: Theoretical Frameworkmentioning
confidence: 99%
“…In order to explore a relevant example of the capabilities required to face the current scenario, deeply transformed by the digital revolution and the pandemic that made clear the need for their application to the workplace, accelerating a process that was still in its infancy, this article refers to a situated organizational case: Comau, an Italian multinational leading company operating in the automotive sector whose activities are strictly connected to the innovative promotion of new capabilities and organizational culture. The Comau experience ( Fregnan et al, 2020 ; Ivaldi et al, 2021 ) identified a set of seven capabilities as a contextualized interpretation of the theoretical framework ( Hecklau et al, 2016 ) and as a transfer into practice of the new culture of work, essential elements to fill the gap that has emerged since the pandemic outbreak:…”
Section: New Work Culture and Capabilities: Theoretical Frameworkmentioning
confidence: 99%
“…When digitalisation is a driver of epistemic complexity, it often comes with an emphasis on standardisation, which may restrict spaces for action on the ground floor. Internationally, studies have argued that there is an increasing gap between the high and low skilled regarding how the "digital revolution" affects their work, where it is claimed that groups of high-skilled workers experience increased autonomy, decision-making power and creative forms of work, whereas lower skilled workers may find work more precarious and subject to stricter standards and control (Ivaldi et al, 2022). At the same time, the way in which digitalisation initiatives bring about a need to reconfigure roles and responsibilities in health services will imply that practices are changed and need to be (re) stabilised on many layers in the organisation, and therefore, they affect most workers.…”
Section: Discussionmentioning
confidence: 99%
“…Whether the characteristics of Nordic working life provide specific conditions for professional learning is an interesting question that cannot be fully answered based on the above described studies. Granting more responsibility and autonomy to workers is seen as important for generating continual learning and organisational improvement in the wake of technological and social change (Ivaldi et al , 2022; Simons and Ruijters, 2014). The examples provided above suggest that many professionals in the Norwegian education and health sectors are granted such opportunities.…”
Section: Discussionmentioning
confidence: 99%
“…However, not everyone is affected equally. High-skilled workers may benefit from greater autonomy and decision-making power, especially in terms of creative work in developing existing work practices, procedures and policies, while low-skilled workers may face greater formalization, standardization and thus tighter control (Ivaldi, Scaratti, & Fregnan, 2021). However, it is important to also give more autonomy to low-skilled workers who are responsible for following certain policies and procedures, as they can serve as a great source of information for future learning and improvement.…”
Section: Nordic Model and Learning Organizationsmentioning
confidence: 99%